Pretreatment of the Antagonistic Yeast, Debaryomyces hansenii, With Mannitol and Sorbitol Improves Stress Tolerance and Biocontrol Efficacy - Ming, Xiaobing; Wang, Yong; Sui, Yuan (Frontiers in Microbiology, 2020)
The effect of exogenous mannitol and sorbitol on the viability of the antagonist yeast, Debaryomyces hansenii, when exposed to oxidative and high-temperature stress was determined. Results indicated that both the 0.1 M mannitol (MT) and 0.1 M sorbitol (ST) treatments improved the tolerance of D. hansenii to subsequent oxidative and high-temperature stress. MT or ST cells had a significantly higher cell survival, enzyme activity, and catalase and superoxide dismutase gene expression level, relative to non-treated, control yeast cells, when exposed to a subsequent oxidative (30 mM H2O2) or heat (40.5 oC) stress for 30 min. Additionally, MT and ST yeast exhibited a higher growth rate in kiwifruit wounds, and a greater ability to inhibit postharvest blue mold (Penicillium expansum) and gray mold (Botrytis cinerea) infections. The present study indicates that increased antioxidant response induced by mannitol and sorbitol in D. hansenii can enhance stress tolerance and biocontrol performance.